FEATURES OF filtering USING COORDINATEd turn models - A. S. Solonar; P. A. Khmarski; A. A. Mikhalkovski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The features Extended Kalman filter using coordinated turn models are considered. The estimation performance of Interacting Multiple Model filter modifications is compared.